American Girl: Kit Learns a Lesson - A School Story - Tripp, Valerie 1951-; Rane, Walter (Middleton, WI : Pleasant Co. Publications, 2000)
In 1934 Kit finds that she has hard lessons to learn about the Depression both at home, where she is helping her mother run a boarding house while her father looks for a new job, and at school, where a fight spoils the preparations for the Thanksgiving pageant.
"Book 2."
"Ages 7 and up"--cover p. [4].
Keywords: Depressions -- Fiction -- 1929; Depressions -- Fiction -- 1929; Schools -- Fiction; Thanksgiving Day -- Fiction; Boardinghouses -- Fiction